2009
DOI: 10.1093/nar/gkp200
|View full text |Cite
|
Sign up to set email alerts
|

DIDS, a chemical compound that inhibits RAD51-mediated homologous pairing and strand exchange

Abstract: RAD51, an essential eukaryotic DNA recombinase, promotes homologous pairing and strand exchange during homologous recombination and the recombinational repair of double strand breaks. Mutations that up- or down-regulate RAD51 gene expression have been identified in several tumors, suggesting that inappropriate expression of the RAD51 activity may cause tumorigenesis. To identify chemical compounds that affect the RAD51 activity, in the present study, we performed the RAD51-mediated strand exchange assay in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 44 publications
3
79
0
Order By: Relevance
“…5,45 Because up-regulation of RAD51 recombinase may cause genomic instability, several approaches have been developed to inhibit/control its activity, for example, protein aptamer derived from BRC4 motif of BRCA2 to inhibit RAD51 filament formation and DNA aptamer and a chemical compound that inhibit RAD51-dependent pairing and strand exchange. [46][47][48] However, these strategies will also target RAD51-mediated HomoRR in normal cells, which may exert a deleterious effect on cell survival and chromosomal stability. 49 Instead, we propose to target the region of RAD51, RAD51(pY315), which is directly phosphorylated by BCR-ABL1 oncogenic kinase, preferentially detected in the nuclei of leukemia, but not normal cells, and involved in HomeoRR.…”
Section: Discussionmentioning
confidence: 99%
“…5,45 Because up-regulation of RAD51 recombinase may cause genomic instability, several approaches have been developed to inhibit/control its activity, for example, protein aptamer derived from BRC4 motif of BRCA2 to inhibit RAD51 filament formation and DNA aptamer and a chemical compound that inhibit RAD51-dependent pairing and strand exchange. [46][47][48] However, these strategies will also target RAD51-mediated HomoRR in normal cells, which may exert a deleterious effect on cell survival and chromosomal stability. 49 Instead, we propose to target the region of RAD51, RAD51(pY315), which is directly phosphorylated by BCR-ABL1 oncogenic kinase, preferentially detected in the nuclei of leukemia, but not normal cells, and involved in HomeoRR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lin, Y W et al have reported a variety of drugs that inhibit the expression of Rad51, such as DIDS [16], erlotinib [17], emodin [18], and gefitinib [19]. Therefore, these drugs can be investigated in future studies, particularly to test if their combination can enhance the therapeutic effect against osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…From now, different assays were adapted for screening Rad51 inhibitors [17,19,20]. To identify chemical compounds that inhibit Rad51 activity, we employed here a different method, which is an electrophoresis-based DNA strand exchange assay as described in Fig.…”
Section: An Electrophoresis-based Dna Strand Exchange Assaymentioning
confidence: 99%
“…Given the involvement of Rad51 in such severe diseases, it represents an important target for anticancer therapy and the development of small molecule inhibitors capable of inhibiting Rad51 activities is warranted. Thence, very recently, few compounds have been identified as inhibitors of Rad51 and the great majority of them have been selected by high-throughput screening from chemical libraries [17][18][19][20]. However, the development of a new drug is a hard and expensive process, including the fact that new drugs have to undergo a challenging approval process by the Food and Drug Administration (FDA) in order to make sure that the drug is safe for consumption.…”
Section: Introductionmentioning
confidence: 99%